2013
DOI: 10.1007/s10792-013-9797-4
|View full text |Cite
|
Sign up to set email alerts
|

The study of etiological and demographic characteristics of pterygium recurrence: a consecutive case series study from Pakistan

Abstract: To determine the agents of recurrence, the demographic features, and the management and outcomes of pterygium cases treated at Aga Khan University Hospital (AKUH), Karachi. This hospital-based descriptive study included 147 patients with pterygium (147 eyes) from both sexes, who presented at the Ophthalmology Department at AKUH between January 1, 2002 and December 31, 2010. Data regarding their demographic profile and other factors were collected in a well-structured proforma. Data were analyzed using frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…These results are in accordance with studies showing that the grade and morphology of pterygium influences recurrence rates when autografting with fibrin glue, in addition, studies showed that there appeared to be significantly more recurrences in the high grade group than the low grade group. [ 11 , 12 ] Our postoperative complication and recurrence results after pterygium surgery compared favourably with the other published studies.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…These results are in accordance with studies showing that the grade and morphology of pterygium influences recurrence rates when autografting with fibrin glue, in addition, studies showed that there appeared to be significantly more recurrences in the high grade group than the low grade group. [ 11 , 12 ] Our postoperative complication and recurrence results after pterygium surgery compared favourably with the other published studies.…”
Section: Discussionsupporting
confidence: 79%
“…It is a challenge to treat Chinese pterygium patients using only glue to fix a CAG because of the high grade and large size of pterygiums in the patients being treated, which may meet severe postoperative inflammation and unstable CAG. Mahar and Manzar [ 11 ] and Sandra et al [ 12 ] reported that there was a definite trend of increased postoperative complication such as recurrence with higher grade of pterygium when autografting with fibrin glue. [ 11 , 12 ] In our Institution, we began using fibrin glue in CAGs in 2014 and have found several complications, such as graft loss/displacement, dehiscence, proliferative granuloma, and pterygium recurrence, which may be due to the abovementioned reason.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From previous literature, it is understood that pterygium size and grade increases the risk of recurrence [25][26][27]. In our cases, it cannot be determined if attendings selected the more complex and higher grade cases.…”
Section: Discussionmentioning
confidence: 82%
“…If this holds true, the attendings' recurrence rates may trend higher due to more difficult procedures and higher risk of recurrence. Younger age also increases the risk for recurrence, but age was not significantly different between the experience groups [25,[28][29][30].…”
Section: Discussionmentioning
confidence: 85%